Photoheterotrophy by aerobic anoxygenic bacteria modulates carbon fluxes in a freshwater lake - Piwosz, Kasia; Villena-Alemany, Cristian; Mujakić, Izabela (The ISME journal, 2022)
Lakes are a significant component of the global carbon cycle. Respiration exceeds net primary production in most freshwater lakes, making them a source of CO2 to the atmosphere. Driven by heterotrophic microorganisms, respiration is assumed to be unaffected by light, thus it is measured in the dark. However, photoheterotrophs, such as aerobic anoxygenic photoheterotrophic (AAP) bacteria that produce ATP via photochemical reactions, substantially reduce respiration in the light. They are an abundant and active component of bacterioplankton, but their photoheterotrophic contribution to microbial community metabolism remains unquantified. We showed that the community respiration rate in a freshwater lake was reduced by 15.2% (95% confidence interval (CI): 6.6-23.8%) in infrared light that is usable by AAP bacteria but not by primary producers. Moreover, significantly higher assimilation rates of glucose (18.1%; 7.8-28.4%), pyruvate (9.5%; 4.2-14.8%), and leucine (5.9%; 0.1-11.6%) were measured in infrared light. At the ecosystem scale, the amount of CO2 from respiration unbalanced by net primary production was by 3.69 × 109 g CO2 lower over these two sampling seasons when measured in the infrared light. Our results demonstrate that dark measurements of microbial activity significantly bias the carbon fluxes, providing a new paradigm for their quantification in aquatic environments.
Keywords: mikrobiota; aerobní bakterie; uhlík; oxid uhličitý; Carbon Cycle; koloběh uhlíku; Bacteria, Aerobic; Carbon Dioxide; Microbiota; Carbon; jezera; Lakes